2014
DOI: 10.1148/radiol.14132084
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Tensor MR Imaging of the Breast: Hormonal Regulation

Abstract: DTI parameters are not sensitive to menstrual cycle changes, while menopause, long-term HRT, and presence of milk in lactating women affected the DTI parameters. Therefore, the timing for performing breast DTI is not restricted throughout the menstrual cycle, whereas the modulations in diffusion parameters due to HRT and lactation should be taken into account in DTI evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 43 publications
2
35
0
Order By: Relevance
“…Another example demonstrating the sensitivity of the tensor to the size of the ducts is shown in the example of a lactating volunteer in Figure 14. Since milk is a colloid of fat globules within a water-based fluid that contains dissolved carbohydrates and protein aggregates with minerals, the viscosity of milk is higher than that of the normal water fluid in the ducts, and thus, the water diffusion coefficients of lactating breasts are lower than those of premenopausal women 24 . Furthermore, the ducts near the nipple are large and the restriction in the directions orthogonal to the ducts is lower than in the non-lactating breast, and consequently the anisotropy indices are lower as well.…”
Section: Representative Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another example demonstrating the sensitivity of the tensor to the size of the ducts is shown in the example of a lactating volunteer in Figure 14. Since milk is a colloid of fat globules within a water-based fluid that contains dissolved carbohydrates and protein aggregates with minerals, the viscosity of milk is higher than that of the normal water fluid in the ducts, and thus, the water diffusion coefficients of lactating breasts are lower than those of premenopausal women 24 . Furthermore, the ducts near the nipple are large and the restriction in the directions orthogonal to the ducts is lower than in the non-lactating breast, and consequently the anisotropy indices are lower as well.…”
Section: Representative Resultsmentioning
confidence: 99%
“…More recently, diffusion weighted MRI and the resulting maps of apparent diffusion coefficient (ADC) have been evaluated as a complement method to DCE-MRI and it was shown that ADC values can help distinguish between cancers, benign lesions and normal breast tissue 9,10 . In addition, studies of breast diffusion tensor imaging (DTI) were initiated in healthy volunteers and patients with breast lesions at field strength of 1.5 T [11][12][13][14][15] and of 3 T [16][17][18][19][20][21][22][23][24] . Most of these studies reported ADC and fractional anisotropy (FA) values 11,12,14,15,[20][21][22][23] and found these two parameters to be reproducible with ADC values more reproducible than FA 13,20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This requires the standardization of DTI parameters and assessing the normative range as well as improved understanding of factors that influence these values. Few publications have specifically focused on characterizing normal breast tissue [10, 11] and to our knowledge no group has evaluated the effects of fibroglandular tissue composition (FGT) and background parenchymal enhancement (BPE) on DTI measurements. Our goal was to measure DTI parameters at 3T in normal breast tissue and assess the influences of FGT composition and BPE.…”
Section: Introductionmentioning
confidence: 99%
“…These provide a complete description of the geometric and diffusion properties of the tensor [42]. Recent studies [43,44] applying DTI-derived vector and parametric maps indicate that the breast architecture can thereby be evaluated with high spatial resolution. Comparisons between twenty-six women with 33 cancerous breast lesions and fourteen women with 20 benign breast lesions revealed lower (p < 0.0009) orthogonal diffusion coefficients λ 1 , λ 2 , λ 3 in the malignant lesions, with a specificity of 98 %.…”
Section: Diffusion-weighted Mri For Breast Cancer Diagnosticsmentioning
confidence: 99%